The complex impact of auditory error direction, magnitude, and exposure on corrective responses - Sreedhar, Anuradha J.; Daliri, Ayoub (Frontiers in Human Neuroscience, 2026)
PurposeWhen encountering errors, the brain produces within-production corrective responses to compensate for the errors. The brain also develops adaptive responses to ensure the accuracy of future productions. This study examined the impact of the number of exposures to errors with different characteristics on corrective and adaptive responses.MethodsWe designed a compensation paradigm to apply three perturbation magnitudes in two directions within the two-dimensional formant space: (1) a concurrent increase in the first formant and decrease in the second formant, acoustically shifting /ɛ/ toward /æ/ (ɛ-to-æ perturbations), and (2) a concurrent increase in the first formant and increase in the second formant, shifting /ɛ/ toward the outside of the vowel space (ɛ-to-out perturbations). To calculate corrective responses in perturbed trials, we determined the difference between formants in the late (300–400 ms) and early (0–100 ms) intervals of the vowel. We estimated adaptive responses in unperturbed trials by calculating formant changes in the early interval of the post-perturbation trial relative to the early interval of the pre-perturbation trial. We examined the responses in the first and second halves of trials in each condition to determine the effect of exposure to perturbations.ResultsWe found that (1) corrective responses to ɛ-to-æ perturbations were larger and proportionally larger for small perturbations in the first half of perturbed trials, (2) adaptive responses were measurable after exposure to a single perturbation, and (3) strikingly, both corrective and adaptive response directions were generally in the participant-specific ɛ-ɪ direction, regardless of the perturbation direction. This preferred response direction was in the opposite direction of the ɛ-to-æ perturbations but was perpendicular to the ɛ-to-out perturbations.ConclusionOur findings suggest that the brain responds more to small and natural-sounding errors (ɛ-to-æ perturbations) than large and unnatural errors (ɛ-to-out perturbations). The brain’s biases in selecting movements may influence error compensation, leading to responses that prioritize preferred movements even when they do not fully correct errors (e.g., responding in the ɛ-ɪ direction for ɛ-to-out perturbations). Finally, as the brain encounters more unexpected errors, it may evaluate them differently and respond less to them.